Progress of the Personal Income Tax in Emerging and Developing Countries - Benedek, Dora (IMF Working Papers; Working Paper ;, 2022)
Personal Income Tax (PIT) is one of the key sources of revenues in Advanced Economies (AEs) but plays a much more limited role in Low-Income Developing Countries (LIDCs) and Emerging Market Economies (EMEs), both in terms of revenue and redistributive impact. Notwithstanding, this paper shows that LIDCs and EMEs increased their PIT-to-GDP revenue by 110 and 48 percent, respectively, during the 1990-2019 period, a marked improvement in the PIT revenue performance. We find that this rise was driven primarily by economic developments and to a lesser extent by changes in the design of PIT systems. We also find that LIDCs that improved their tax-to-GDP ratios relied on a broader set of tax instruments and not exclusively on the PIT, suggesting that a successful revenue mobilization strategy of developing countries requires a comprehensive approach covering a wider range of taxes. Finally, using a newly assembled dataset of PIT characteristics of 157 countries over the 2006-2018 period, we estimate a novel redistribution index of the PIT in LIDCs. We show that the contribution of the PIT to inequality reductions has been significant.